Wild vertebrates’ roadkill across on roads in southeastern Mexico - Briceño Mendez, Marcos Alberto; Montiel Ortega , Salvador; Contreras Perera, Yamili Jazmin; Sánchez-Zavalegui, Romeo (Ecosistemas y Recursos Agropecuarios, 2025)
Roads are terrestrial communication routes that promote economic and social development worldwide. However, they also represent often deadly crossing spaces for wildlife, which can die from collisions. Assessed the mortality of wild vertebrates killed by vehicle collisions on two highway sections (Hopelchen-Dzibalchen and Dzibalchen-Xpujil), in the state of Campeche, Mexico. In the 156 km evaluated, a total of 142 animals were hit by cars, classified into 28 species of wild vertebrates: mammals (54%), reptiles (25%), birds (17%) and amphibians (4%). At least 14% of the recorded species are protected by Mexican legislation. That wildlife accidents were not associated with the season, but 19 points along the road were identified with more registered cases. The mammals are most affected by vehicle accidents, especially at road points where it is recommended to install road signs to prevent wildlife accidents, such as human settlements and protected areas such as the Calakmul Biosphere Reserve